A CASE-CONTROL STUDY EXPLORING SERUM HOMOCYSTEINE LEVELS IN NON-DIABETIC ISCHEMIC STROKE PATIENTS. - Durgeshwar, Kumar; Kumar, Sanjeev; Kumar, Naween; U. C. Jha (Student's Journal of Health Research Africa, 2023)
Aim: The purpose of the present study was to evaluate the serum levels of homocysteine in individuals diagnosed with idiopathic ischemic stroke and to establish a correlation between its clinical relevance and other risk factors associated with ischemic stroke. Methods: This case-control design study was conducted at the Department of Medicine, DMCH, Lehariasarai. The study comprised a total of 21 individuals diagnosed with non-diabetic ischemic conditions, alongside 21 controls. Inclusion criteria included individuals of adult age, who exhibited no prior diagnosis of diabetes and presented with first-ever ischemic stroke. Confirmation of the ischemic stroke was confirmed through CT scanning of the cranial region. Exclusion criteria consisted of individuals diagnosed with diabetes mellitus, haemorrhagic stroke, individuals who encountered an embolic stroke, receiving vitamin supplementation, and phenytoin usage. The patient underwent regular examinations, including serum homocysteine level and fasting serum lipid profile assessment. Results: The male patient population exhibited a higher prevalence (61.9%) in comparison to the female patient population (38.1%). The majority of patients (62.3%) fell in the age group of less than 60 years. The prevalence of male patients was higher across all age groups, with the exception of the age group spanning from 30 to 40 years. Conclusions: A statistically relevant correlation was found among all the investigated factors for risk in non-diabetic individuals and the levels of serum homocysteine. Recommendation: The assessment of serum homocysteine levels is strongly advised for the comprehensive evaluation of idiopathic ischemic strokes, with the aim of conducting a prognostic assessment.